2004
DOI: 10.1007/s00428-004-1125-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of cartilage-specific matrix protein chondromodulin-I mRNA in salivary pleomorphic adenomas

Abstract: Pleomorphic adenoma is the most common epithelial tumor in the salivary glands. This tumor frequently exhibits "mesenchyme"-like components, including myxoid or chondroid areas. Recently, using immunohistochemical techniques, we reported that cartilage-specific matrix protein, chondromodulin-I (ChM-I), was deposited on the inter-territorial matrix of the chondroid area in salivary pleomorphic adenomas and that ChM-I, which is also a strong angio-inhibitory factor, plays an important role in the avascular natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Pleomorphic adenoma of the salivary glands is characterized by the mixed appearance of epithelial and mesenchymal-like elements, and the expression of ChM-I in this disease is associated with the formation of chondroid elements and inversely correlates with the presence of a CD34 endothelial marker [79,80]. This suggests that ChM-I is involved in both hypovascularity and in chondroid differentiation in this type of tumor.…”
Section: Use Of the Chm-i Domain As A Therapeutic Target And Its Actimentioning
confidence: 91%
“…Pleomorphic adenoma of the salivary glands is characterized by the mixed appearance of epithelial and mesenchymal-like elements, and the expression of ChM-I in this disease is associated with the formation of chondroid elements and inversely correlates with the presence of a CD34 endothelial marker [79,80]. This suggests that ChM-I is involved in both hypovascularity and in chondroid differentiation in this type of tumor.…”
Section: Use Of the Chm-i Domain As A Therapeutic Target And Its Actimentioning
confidence: 91%
“…1 This paper adds to several others published in recent years on distinguishing primary serosal neoplasms from metastases originating from lung and extrapulmonary carcinoma. [2][3][4][5][6][7] As pointed out by these studies, positive and negative mesothelioma markers do not have universal diagnostic usefulness, since their specificity and sensitivity vary according to individual conditions. The use of a small panel of antibodies with a high combined sensitivity and specificity is therefore recommended.…”
Section: Claudin-4 In Mesothelioma Diagnosismentioning
confidence: 99%
“…PA is a hypovascular tumour due to the low density of CD34+ endothelial cells 3 . We have previously reported that cartilage‐specific matrix protein, chondromodulin‐I (ChM‐I) protein and mRNA are expressed in PA 3,4 . ChM‐I serves as a barrier against angiogenic factors, providing a possible explanation for PA being a hypovascular tumour.…”
Section: Antibodies Used For Markers In Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation